Evaluation of ceramic lab facilities layout design of KKTM Masjid Tanah using SLP method - Tahrel, Azrin (2014)
Facilities layout design is a significant factor contribute to the efficient manufacturing systems. A good design in facility layout may reduce travel time, expedite flow of material, operators and tools. It greatly affects the system performance of an organization. This study is related the facilities layout at the Ceramics Workshop, KKTM Masjid Tanah, Melaka. The reliable layout of this workshop is required to support Production-Based Education (PBE) practiced in KKTM, especially when PBE program run entirely by high volume products. The current layout of workshop is not appropriate to support the activities as the flows of material of different products produced are not considered. The objective of this study was to redesign a new layout of the Ceramic workshop using Systematic Layout Planning (SLP) method and suggests of improvements designed layout. Data collection was performed such as the flow of process for each product, the area of each station, the distances between the regions. SLP is widely used in manufacturing industries to plan the layout of the facility. SLP procedures are based on data input of production activities, the flow of materials, relationship activities, relationship diagram, the need for space, spatial relationships diagram, modifying considerations and limitations, development and evaluation of alternative layouts. The study proposes some alternatives layout for improvement. Based on minimum distance criteria the alternatives were evaluated. Each layout alternative has its own advantages. Therefore, a decision was made where alternative number 2 is suggested as it is more effective layout in terms of flow, and distance.